Pelaksanaan Prinsip-Prinsip Demokrasi dalam Pengambilan Keputusan: Studi Pada Kepala Kampung Nambah Dadi Kecamatan Terbanggi Besar Kabupaten Lampung Tengah - Aliyandi, Aliyandi (Tapis: Jurnal Penelitian Ilmiah, 2019)
The Decision-Making Process in society is said to be Democratic if its implementation passing mechanisms that involve the community in its formulation intensively and can reflect the demands and desires of the community without ignoring their rights. However, the act of determining an individualism decision is a hallmark of undemocratic patrimonial bureaucracy. This must be considered by every leader, including in Kampung Nambah Dadi in accordance with realizing checks and balances based on the Principles of Democracy. Therefore, this study was conducted to determine the Democracy principle of Decision Making in Kampung Nambah Dadi Terbanggi Besar District, Central Lampung Regency. Based on the results of a qualitative descriptive analysis revealed that there is a decision-making process according to equal rights principles, by holding the meetings with society and Village Consultation Council (BPK). However, BPK's ability as supervision in Nambah Dadi has not been in line with expectations. This condition is caused by the headman domination power effect.